Association between Follicular Fluid Leptin and Serum Insulin Levels in Nonoverweight Women with Polycystic Ovary Syndrome. (4th May 2014) - Garruti, G.; de Palo, R.; Rotelli, M. T.; Nocera, S.; Totaro, I.; Nardelli, C.; Panzarino, M. A.; Vacca, M.; Selvaggi, L. E.; Giorgino, F.
Abstract : Aims . We evaluated the links between leptin and visfatin levels and fertilization rates in nonoverweight (NOW) women with PCOS (NOW-PCOS) from Apulia undergoing in vitro fertilization/embryo transfer (IVF). Materials and Methodology . We recruited 16 NOW women with PCOS (NOW-PCOS) and 10 normally ovulating NOW women (control-NOW). All women underwent IVF. Androgens, 17- β -estradiol (17 β -E2 ), and insulin levels were measured in plasma and/or serum and leptin and visfatin levels were assayed in both serum and follicular fluid (FF-leptin, FF-visfatin). Results . In NOW-PCOS, both serum and FF-leptin were significantly lower than in control-NOW. In NOW-PCOS, significant correlations were found between BMI and serum leptin and insulinemia and FF-leptin. By contrast, in control-NOW, FF-leptin levels were not correlated with insulinemia. Serum visfatin levels were not significantly different in NOW-PCOS and control-NOW, but FF-visfatin levels were 1.6-fold higher, although not significantly, in NOW-PCOS than in control-NOW. Conclusions . Both serum leptin levels and FF-leptin are BMI- and insulin-related in Southern Italian NOW-PCOS from Apulia. In line with other reports showing that FF-leptin levels are predictive of fertilization rates, lower than normal FF-leptin levels in NOW-PCOS may explain their lower fertilization rate and this may be related to the level of insulin and/or insulin resistance.